Genomic approaches and prospects for breeding flood-tolerant rice in Africa - Bulegeya, Victoria; Kilasi, Newton; Hussain, Waseem; Murori, Rosemary; Bilaro, Atugonza; Ismail, Abdelbagi; Nchimbi-Msolla, Susan (Taylor & Francis, 2025)
Flooding is among the most devastating abiotic stresses for food crops, recently aggravated by climate change, especially in rainfed rice-producing areas of Africa. Breeding for tolerance to flooding stress has been slow, with flood-tolerant varieties released in few countries. This review explores the status of breeding efforts for flooding tolerance improvement in Africa, summarizing the progress made, identifying breeding gaps, and highlighting available breeding opportunities. The review also pinpoints the existing genomic resources, including key genes and QTLs for flooding tolerance, such as SUBMERGENCE 1 (SUB1) for complete submergence, SNORKEL 1 (SK1) and SNORKEL 2 (SK2) for deep water flooding,and qAG-9-2 (AG1) and qAG-7-2 (AG2) for anaerobic germination. These genetic resources provide a valuable platform for African breeders to incorporate multiple stress tolerance traits into elite cultivars. Consequently, we emphasized the need for integrating modern breeding tools with traditional breeding methods to expedite the deployment of flood-tolerant varieties in Africa.